- Angka Pemberdayaan Kader Dan Keluarga Dalam Pengenalan Dan Penanganan Tanda-Tanda Bahaya Kehamilan Pada Ibu Hamil Dalam Upaya Menurunkan Tingkat Kejadian Abortus Di Wilayah Kerja Puskesmas AstambulKematian Ibu (AKI), abortus, pendidikan kesehatan, tanda bahaya kehamilan: - - sajidah, ainun; Hammad; Parellangi; Azhima, Rizkan; Dewi, Rima; Huda, Nadwa (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
The Maternal Mortality Rate (MMR) in South Kalimantan Province, particularly in Banjar Regency, has shown an increase from 2018 to 2023. In 2018, the MMR was recorded at 108 per 100,000 live births, up from 103.9 in the previous year. By 2023, Banjar Regency reported 199 cases of MMR, ranking it as the third-highest region in the province. The leading causes of maternal deaths were hemorrhage and hypertensive disorders in pregnancy. In Pasar Jati Village, Astambul District, Banjar Regency, there were 6 cases of abortion in 2023, the highest among 22 villages in the district. Research indicates a strong correlation between abortion and pregnancy risk factors, with 32.95% of pregnant women having high-risk factors and 18.19% having very high-risk factors. Out of 197 pregnant women, 25 had a history of abortion with high or very high-risk factors. Health education is considered an effective strategy to enhance public awareness and knowledge about abortion and pregnancy danger signs. Studies show that health education significantly improves knowledge among pregnant women, particularly primigravida, regarding pregnancy risks and abortion prevention. Providing information early in pregnancy can better prepare mothers and reduce the risk of complications. Community service results demonstrated an increase in respondents' knowledge about pregnancy danger signs and abortion management, with p-values of 0.016 for families and 0.002 for health cadres. Thus, health education is a crucial intervention in efforts to reduce MMR and improve maternal well-being. Keyword : Maternal Mortality Rate (MMR), abortion, health education, pregnancy danger signs